Time in the Quran story Psychological time: Case Study - Yasouf, Ahmed; Abd al- Rahim, Yasser; Ayoubi, Fatema (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research deals with time psychology in stories of the Holy Quran. It begins with defining time psychology and shows its kinds and their reasons, from a personal and internal time and the time of ego. Then the research moves on to reveal the time psychology in Arabic Literature and it begins with poetry. It displays some lines of verse that illustrate the sense of time, and then it clarifies the meaning of time psychology in the new narrative studies. After that, the research deals with time psychology in the story of the Holy Quran and the wrong estimate of time due to not realizing it because of the loss of loss of life, or unconsciousness. Then it exposes some human moments of different characters from the Holy Quran, like incidents of drowning, giving birth, moments of fear and worry, moments of departure and meeting and the moments of determining and triumph. The research demonstrates that the story in the Holy Quran can transmit human feelings, explain emotions and express psychological senses and the inner depths of the characters, using words with high level of transparency and subtlety. The words are meaningul and carefully chosen. So, all of that what has probably given the miraculous story of the Holy Quran it’s superiority in both it’s linguistics and semantics. Also, it exceeds high above the limited level of the human capacity.